IMPLEMENTASI MODEL PIDANA KERJA SOSIAL BERBASIS NILAI-NILAI HUKUM ADAT SUNDA - Yustia, Rd. Dewi Asri; Batubara, Gialdah Tapiansari; Ludiana, Tia (Faculty of Law, Universitas Pasundan, 2021)
Criminal sanctions against perpetrators of corruption crimes require extraordinary breakthrough according to the penal objectives, which is not only to provide a deterrent effect for the perpetrators, but also to provide benefits to the community by optimizing the competencies held by the perpetrators, since perpetrators of corruption are competent either in the aspects of social, economics and politics. The current criminal sanctions do not lead to the utilization of the potential possessed by the perpetrators of criminal acts. The focus still leads to deter the perpetrators only by providing severe criminal sanctions, namely by accumulating criminal sanctions in prison and fines, as well as other additional sanctions that focus on perpetrators, not on to interests of the state and society. The result of the research is to conceive the concept of social work sanctions that utilize the competence/expertise of the perpetrators to be able to provide great benefits to the community directly which implementation is based on the values ​​contained in Sundanese customary law, so that the objectives of the punishment are not only to correct the conduct of the perpetrators, but also to restore state financial losses, and to provide great benefits for the community. Keywords: Sanction of Community Service, values, Sundanese Customary Law, Purpose of Punishment.